Ganti Rugi Korban Kecelakaan Pesawat Udara: Tanggung Jawab Maskapai atau Produsen Pesawat? (Studi Kasus Sriwijaya Air SJ 182): Compensation for Victims of Sriwijaya Air SJ182 Accident: Airline or Aircraft Manufacturer Responsibility? - Dhafin Ramadhan; Rachminawati Rachminawati (Faculty of Law, Maranatha Christian University, 2025)
The Sriwijaya Air SJ 182 plane crash killed 62 passengers and cabin crew. For the death of passengers, the airline gave compensation to the victims of the plane crash. Some passengers accepted, but some refused because they wanted to sue Boeing as the aircraft manufacturer in the United States national court. This research attempts to analyse which party actually has the responsibility in providing compensation to victims of aircraft accidents. This research uses a normative juridical approach with an analytical descriptive method. This research uses the literature research method, with the main focus on primary, secondary, and tertiary legal sources. International law that regulates the responsibility for compensation of victims of aircraft accidents, namely the Warsaw Convention 1929 and the Montreal Convention 1999, only regulates airlines as the responsible party so there is a legal gap. Indonesian national law, which is supposed to fill the existing legal gap, also does not regulate the responsibility of aircraft manufacturers and only regulates the responsibility of airlines as the main carriers. Other countries such as the United States and the European Union fill the legal vacuum by using Consumer Protection Law, but this has not been implemented in Indonesia. The author concludes that there is a need for aviation regulatory reform at both the national and international levels that further regulates the liability of aircraft manufacturers to promote justice for victims and improve the security and safety of the global aviation industry.